2021
DOI: 10.1186/s13018-021-02422-5
|View full text |Cite
|
Sign up to set email alerts
|

Potential role of m6A RNA methylation regulators in osteosarcoma and its clinical prognostic value

Abstract: Background Osteosarcoma is a disease with high mortality in children and adolescents, and metastasis is one of the important clinical features of osteosarcoma. N6-Methyladenosine (m6A) is the most abundant methylation modification in mRNA, which is regulated by m6A regulators. It is reported that it is related to the occurrence and development of tumors. However, the mechanism of its action in osteosarcoma is rarely known. The purpose of this study was to identify the potential role of m6A regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 48 publications
1
9
0
Order By: Relevance
“…The m6A methyltransferase METTL3 has been reported to promote the progression of various cancers, including bladder cancer and lung cancer, through modulating the expression of microRNAs or mRNAs [25] , [26] . The similar mechanism was observed in OS as well [27] , [28] , [29] , [30] , [31] . In this study, through m6A-seq, we revealed that the m6A enrichment region was distributed around the exon, while METTL3 poorly expressing OS cells showed more deposition of m6A in the 5′UTR and 3′UTR.…”
Section: Discussionsupporting
confidence: 79%
“…The m6A methyltransferase METTL3 has been reported to promote the progression of various cancers, including bladder cancer and lung cancer, through modulating the expression of microRNAs or mRNAs [25] , [26] . The similar mechanism was observed in OS as well [27] , [28] , [29] , [30] , [31] . In this study, through m6A-seq, we revealed that the m6A enrichment region was distributed around the exon, while METTL3 poorly expressing OS cells showed more deposition of m6A in the 5′UTR and 3′UTR.…”
Section: Discussionsupporting
confidence: 79%
“…ALKBH5 attenuates the m6A modification of PVT1 mRNA and impedes the binding of YTHDF2 to PVT1 mRNA, which increases PVT1 expression and accelerates OS growth in vivo [ 13 ]. In addition, m6A-related enzymes are involved in regulating the pluripotency of OS stem cells [ 31 , 32 ]. All these imply potential roles of m6A methylation in tumorigenesis and progression of OS.…”
Section: Discussionmentioning
confidence: 99%
“…Numbers of most of the immune cells (type M1 and M2 macrophages, CD8+ T cells, Tregs, and dendritic cells) were negatively associated with IGF2BP2 expression in osteosarcoma ( 146 ). M 6 A modification-mediated aberrant activation of cell cycle-related pathways and suppression of immune response may play a crucial role in the progression of osteosarcoma ( 147 ).…”
Section: Associations Of M 6 a Rna Methylation With Tumor Immunity In Various Cancersmentioning
confidence: 99%